Usefulness of apheresis to extract microfilarias in management of loiasis. Issue 6391 (20th August 1983) - Muylle, L; Taelman, H; Moldenhauer, R; Van Brabant, R; Peetermans, M E
Abstract : Two patients with loiasis in whom treatment with diethylcarbamazine had to be interrupted because of serious side effects underwent apheresis to extract microfilarias from the blood. After three apheresis sessions the number of microfilarias in the blood had dropped from 8980 to 3412/ml in one patient and from 2950 to 1840/ml in the other. Between 40 and 45 X 10(6) microfilarias were removed from each of the patients. After reduction of the parasitaemia the two patients were given diethylcarbamazine; no appreciable side effects occurred, and the patients were cured.